Robust polyamide-PTFE hollow fibre membranes for harsh organic solvent nanofiltration - Francis, Verona Nithya (2023)
Polymeric membranes have been extensively studied for organic solvent nanofiltration (OSN) but many fail to show sufficient chemical resistance in strong solvents like dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). This study focuses on harnessing the outstanding chemical resistance of polytetrafluoroethylene (PTFE), to develop polyamide-PTFE thin film composite (TFC) membranes that are resistant to such aprotic solvents. A defect-free polyamide thin film layer was successfully synthesized on the microfiltration PTFE hollow fibre substrates, overcoming challenges such as large and uneven pore size, and hydrophobicity of the PTFE substrates. A simple polydopamine (PDA) coating was carried out to improve the substrate's hydrophilicity prior to the polyamide synthesis via interfacial polymerization (IP). Polyethyleneimine (PEI) and trimesoyl chloride (TMC) were used as the monomers and a two-time IP method was employed to obtain a defect-free polyamide coating. The synthesized membranes showed high acetonitrile (ACN) and DMF permeabilities of 7.94 and 3.70 lm−2h−1bar−1, respectively, with acid fuchsin (585 Da) rejections of > 90 %. The molecular weight cut-off (MWCO) of the membranes could be further reduced to ∼300 Da by the addition of piperazine (PIP) monomers. The membranes also showed excellent stability and performance in a 72-hour OSN test performed in DMF indicating their great potential in effective molecular separation in harsh solvents. This study demonstrates how a simple modification and coating technique can transform commercially available microfiltration PTFE hollow fibres into durable and high value OSN membranes.